Design of a Cone‐Cone Shear Cell to Study Emulsification Characteristics. Issue 2 (18th December 2014) - Merkel, Tobias; Emin, M. Azad; Schuch, Anna; Schuchmann, Heike P.
Abstract In order to study emulsification phenomena, devices generating well‐defined flow conditions are essential. Thus, emulsification of drop collectives under laminar shear flow is commonly performed in cylindrical Couette or Searle devices. In these devices, the flow conditions in the shear gap and in the volume underneath the rotor are often different, which can lead to inhomogeneous product properties and may complicate sample taking. Here, a novel cone‐cone shear cell is presented to study emulsification processes. The flow inside the device is examined using numerical simulations. The numerical simulations indicate that simple shear flow is realized all over the sample volume in the cone‐cone shear cell. The experimental results show that the drop breakup in the cone‐cone shear cell is equivalent to the breakup under simple shear realized in the shear gap of a conventional device, i.e., the Searle device. Critical capillary numbers are calculated from the experimental data and show breakup behavior as predicted by single‐drop experiments. Thus, the cone‐cone shear cell proved to be suitable to study emulsification mechanisms in simple shear flow.